The Attitudes-Behaviors Corrective (ABC) Model of Violent Extremism - Khalil, James (Terrorism and political violence, 2022)
Progress in understanding and responding to terrorism and violent extremism has continued to stall in part because we often fail to adequately conceptualize the problem. Perhaps most notably, much of our terminology (for instance, “radicalization”) and many variants of our existing models and analogies (including conveyor belts, staircases and pyramids) conflate sympathy for this violence with involvement in its creation. As its name suggests, the Attitudes-Behaviors Corrective (ABC) model seeks to overcome this issue by placing this key disconnect between attitudes and behaviors at its core. In this paper, we first present the key elements of our model, which include a graphic representation of this disconnect and a classification system of the drivers of violent extremism. The former enables us to track the trajectories of individuals in relation to both their attitudes and behaviors, while the latter helps ensure that we consider all potential explanations for these movements. We then adapt these elements to focus on exit from violence, applying the dual concepts of disengagement and deradicalization. Finally, we conclude with a section that aims to provide the research community and those tasked with preventing and countering violent extremism with practical benefits from the ABC model.